A comparison of rolled, coarse and fine ground milo grain for fattening steer calves. - Cox, R.F.; Smith, E.F. (Kansas Agricultural Experiment Station, 2012)
This is a progress report on full feeding rolled, coarse ground, and fine ground milo grain to steer calves. The test will be completed in July, 1951 when the steers will have been on full feed about 225 days. The objective of the test is to determine which is the most profitable method of preparing milo grain for full feeding, rolling, coarse grinding, or fine grinding.
Keywords: Beef; Milo; Steer; Cost of production